2016
DOI: 10.1038/srep27398
|View full text |Cite
|
Sign up to set email alerts
|

The alterations in the extracellular matrix composition guide the repair of damaged liver tissue

Abstract: While the cellular mechanisms of liver regeneration have been thoroughly studied, the role of extracellular matrix (ECM) in liver regeneration is still poorly understood. We utilized a proteomics-based approach to identify the shifts in ECM composition after CCl4 or DDC treatment and studied their effect on the proliferation of liver cells by combining biophysical and cell culture methods. We identified notable alterations in the ECM structural components (eg collagens I, IV, V, fibronectin, elastin) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 37 publications
7
102
1
Order By: Relevance
“…The content of ECM structural proteins, collagen, elastin, fibronectin and fibrillin are altered in damaged liver. The resulting changes in tissue stiffness may facilitate regeneration or fibrosis (Klaas et al, 2016). …”
Section: Elastin In Healthy and Fibrotic Livermentioning
confidence: 99%
See 1 more Smart Citation
“…The content of ECM structural proteins, collagen, elastin, fibronectin and fibrillin are altered in damaged liver. The resulting changes in tissue stiffness may facilitate regeneration or fibrosis (Klaas et al, 2016). …”
Section: Elastin In Healthy and Fibrotic Livermentioning
confidence: 99%
“…β-aminopropionitrile, the inhibitor of LOX, partially abolishes the increase in liver stiffness and α-SMA expression (Georges et al, 2007). Elastin fibers are formed later (Klaas et al, 2016). Fibrillin-1 expression in portal fibroblasts and in liver MFBs cultured in restrained collagen gel lattices is larger than that in the cells embedded in freely floating lattices (Lorena et al, 2004).…”
Section: Elastin Synthesis and Degradationmentioning
confidence: 99%
“…When ECM fibers were resolved and examined with high quality SEM nanoimages,two distinct types of fibers were clearly visible; one was formed due to CCl4 and the other was formed due to ethanol. These fibers are native to the ECM of various tissues specifically accumulated when tiises are under abnormal or diseased condition [17,18]. the effect of CCl 4 and ethanol became visible bright red in color ( Figure 1b).…”
Section: Discussionmentioning
confidence: 98%
“…He et al ( ) showed that serum levels of HA, procollagen III, and type IV collagen were elevated in patients with hepatitis B virus‐related ALF compared with those with chronic hepatitis B or cirrhosis. ECM proteins are needed for liver regeneration during the physiologic wound‐healing process known as “liver fibrosis.” ( ) However, overactivation of HSCs, the main producers of hepatic ECM, may intensify liver injury and hinder liver regeneration. ( ) HSCs relay inflammatory signals ( ) ; they have also been shown to participate in inflammatory macrophage differentiation and local proliferation in a murine concanavalin A acute liver injury model.…”
Section: Discussionmentioning
confidence: 99%